Psychosocial Perspectives on Working Conditions among Men and Women in Reindeer Breeding in Sweden - Edin-Liljegren, Anette; Daerga, Laila; Sahlén, Klas-Göran; Jacobsson, Lars (Journal of Northern Studies, 2018)
Objective: The aim of this project was to describe the work organisation in the Sami communities and in reindeer-herding work and to explore the range of female duties and compare how men and women experience their psychosocial working conditions. Design: A kind of intervention study was performed by means of a questionnaire sent out to 200 individuals from seven Sami communities. Questions were asked about work organisation, communication, personal relations, solitary work, support, participation and appreciation from colleagues and women’s tasks. Meetings and discussions were held about what was perceived as being important in the life of the Sami communities. Notes from 16 group discussions were written down and analysed according to themes of topics relating to how men and women in the Sami communities experience their lives. Results: Communication and relations were described as being inadequate and some respondents experienced a heavy workload. The women reported more troubled relations, less participation in decision-making and less appreciation from colleagues. Positive issues reported were the Sami identity and a strong connection to the reindeer and to nature. Conclusions: This study indicates a need for a more systematic study of the psychosocial work conditions in the Sami communities in Sweden. Measures should be taken to develop the organisation of work, e.g. through developing communication strategies and conflict management, which has been requested by several Sami communities.